The Family and Community Medicine revised - Gusso, Gustavo (2016)
We have assumed as editors of the Brazilian Journal of Family and Community Medicine (RBMFC) for almost a year. During this period we have tried to implement a management reform in order to gain efficiency. At the same time, we modified some flows, suppliers, office and scope.